Crystal structure of catena-poly[aqua-(μ 2(3,4-dimethylthieno[2,3-b]thiophene-2,5-dicarboxylato-κ 2 O:O′)-(3,6-bis(4′-pyridyl)-1,2,4,5-tetrazine-κ 1 N)zinc(II)], C22H16N6O5S2Zn - Liu Nana; Yang Fei; Wang Suna (Zeitschrift für Kristallographie - New Crystal Structures)
C22H16N6O5S2Zn, monoclinic, C2/c (no. 15), a = 27.068(3) Å, b = 12.4186(11) Å, c = 13.9382(12) Å, β = 102.407(3)°, V = 4575.8(7) Å3, Z = 8, R gt(F) = 0.0454, wRref (F 2) = 0.1180, T = 298 K.